Fast Unbalanced Three-phase Adjustment Base on Single-phase Load Switching - Yanwei Zheng; Lisheng Zou; Jian He; Yongyi Su; Zhiquan Feng (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
To balance three-phase loads in distribution network with abundant of single-phase loads, a new wiring method and three-phase loads adjustment policy was proposed in this paper. In the wiring method, a single-phase load was connected with phase A, B and C of trunk line by a controller. When the load of trunk line was unbalanced, the controller will switch the connected single-phase loads from one phase to another to balance it. The minimum count of loads adjustment algorithm and the most balance adjustment algorithm were proposed, which can adjust the three-phase load of trunk line to roughly balance automatically. This method can solve the serious three-phase unbalance problems of the trunk lines with aboundant of single-phase loads. It may instead of capacitive compensation in low voltage distribution network to improve power quality and reduce network losses. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3031